PERAN PEREMPUAN HINDU DALAM PENGELOLAAN KEUANGAN DAN PENERAPAN AKUNTANSI MENUJU KELUARGA HINDU YANG SUKHINAH DI MASA PANDEMI COVID-19 - Made Denny Oktariyana; Putu Ekawati; Ni Wayan Yulianita Dewi (UNHI Press, 2022)
The importance of financial management by Hindu women and the application of household accounting in Hindus, especially during the covid-19 pandemic, aims to increase living standards, the standard of living in question is so that families are always harmonious, sukhinah avoids financial problems, as well as a long-term investment. for families, especially children so that they can receive higher education in the future. Planning will guide Hindu women and invite them to clearly manage what kind of financial future might be achieved in accordance with the dynamics of their current abilities, potential, and income. In the household, women act as wives and housewives who have heavy obligations and responsibilities. The Covid-19 pandemic means that the universe around the world is affected by an epidemic as it is today, then how can yadnya run like the culture in Hindu society in Bali so that it remains sustainable, Ida Rsi Agung said that Hinduism is flexible and universal, and not difficult. run it according to the teachings of Shiva Sidanta. Rong Tiga Kemulan, Taksu, Tri Kahyangan and Padma Tiga. This study uses a qualitative method that uses the theoretical basis of phenomenological studies. Data collection techniques were carried out by observation, in-depth interviews, and documentation. The sampling technique used was purposive sampling. Data validity using triangulation. The results of this study explain that the informants practice accounting in their household and are recorded by their wives. The important role of financial management and application in the family is to distribute income and expenses to meet household needs and prevent families from debt activities.